EMPIRICAL STUDY OF PROFIT MANAGEMENT WITH TAX MOTIVATION IN INDONESIA (CASE STUDY ON CONSUMER GOODS COMPANIES LISTED ON THE STOCK EXCHANGE) - Nisa, Rahmatun; Muda, Iskandar; Khaddafi, Muammar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The destination of the study is to know and analyze the influence of management profit, profitability, leverage, firm size, ownership managerial, ownership institutions, and audit quality of tax avoidance simultaneously. The Population in this study is registered company in sector consumer goods companies on the Indonesia Stock Exchange (IDX) for the period 2016 – 2020. The Sample in this study was determined by using a purposive sampling technique.The type of data used is secondary data and testing the hypothesis used with STATA software. Test results hypothesis prove that many variables that are not taking a positive effect on avoidance tax. Such as variable management profit, size company, ownership managerial, and ownership institutional are negative. Variable profitability, leverage, and audit quality show the opposite result of this research is positive.